Resistance, innovation and clinical practice in Nise da Silveira's thoughts and actions - Eliane Dias de Castro; Elizabeth Maria Freire de Araújo Lima; Helena Bononi (Faculdade de Medicina de Botucatu (Unesp), 2007)
In the 40s hegemonic psychiatry in Brazil turned to scientific and technological innovations and to the consolidation of an organic vision of mental illness. Within this context, Nise da Silveira researched the development of a clinical practice in the field of occupational therapy and analyzed results with an open mind. She organized and cared for the spaces and time required to develop mental patients' creative capacities, experimentation and artistic learning. The high number and quality of the drawings and paintings produced in her studios triggered intense scientific and artistic interest. Her work changed the monotonous and repetitive activities conducted within the framework of a mental hospital by bringing them closer to patients' actual needs and creating new possibilities of activity and participation in the world. Her work is a benchmark for current practices in occupational therapy. Art, culture and madness have acquired new meanings after her.